Ethical and methodological issues in researching young language learners in school contexts - Pinter, Annamaria; Kuchah, Kuchah, 1970- (Early language learning in school contexts, 2021)
"This book focuses on ethical and methodological issues encountered by researchers working with young language learners in school contexts. The chapters are written by researchers working with children in different classroom contexts around the world and highlight how ethical dilemmas and tensions take on a complex form in child-focused research"--